Caracterização genotípica e fenotípica de Candida sp de fluido vaginal de mulheres adultas - Cunha, Keith Cássia da (2010)
Candida albicans is widely recognized as the pathogen often occurring in vulvovaginal candidiasis. Objective: To compare the genotypes, among infection or colonization and recurrent isolates, with virulence determinants (phospholipase, proteinase, amylase, gelatinase, haemolysin, thermotolerance and biofilm), and to in vitro antifungal susceptibilities. Methods: 317 samples of vaginal fluid of were collected from women with or without symptomatic indications to VVC, including vaginal itching, abnormal discharge, soreness and dyspareunia to mycological investigation. The antimicrobial susceptibility was evaluated for 4 drugs (fluconazole, Itraconazole, ketoconazole and amphotericin B, by dilution method (M27A2- CLSI). Yeasts were subjected PCR (polimerase chain reaction), RAPD (randomly amplified polymorphic DNA), and to RFLP (Restriction fragment lenght polymorphic), this last one, used for identification of Candida dubliniensis. Results: Considering the prevalent species, C. albicans showed high rates of significant sensitivity to azoles and the vast majority of produced virulence factors, regardless of their origin, infection or colonization. Statistical analysis enabled identification of 17 clusters with identical genetic identity, and other moderately related, or unrelated. Conclusions: There was no correlation between the genetic patterns with virulence and antimicrobial susceptibility for all isolates, suggesting that, the amplified genetic regions do not match with variables and might be related to other biological events. The inclusion of other primers could allow higher association among C. albicans strains.